1978
DOI: 10.1111/j.1432-1033.1978.tb12457.x
|View full text |Cite
|
Sign up to set email alerts
|

The Conformation of Histone H5

Abstract: Treatment of chicken erythrocyte histone H5 with trypsin in a high-ionic-strength medium results in very rapid initial digestion and the formation of a 'limiting' resistant product peptide. Under these solution conditions the H5 molecule is maximally folded by spectroscopic criteria and it is concluded that the resistant peptide, GH5, represents a globular folded region of the molecule whilst the rapidly digested parts are disordered. The peptide GH5 is shown to comprise the sequence 22-100. In support of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
0

Year Published

1980
1980
2005
2005

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(80 citation statements)
references
References 24 publications
6
74
0
Order By: Relevance
“…September 1980 and Serz9 in H5) which are located inside the structured apolar regions of the proteins [28,29], are brought to the surface of the protein by a &turn structure and therefore are accessible to the protein kinase [ 131. The major sites of phosphorylation are placed outside the organised apolar regions of the proteins [29].…”
Section: Febs Lettersmentioning
confidence: 99%
See 1 more Smart Citation
“…September 1980 and Serz9 in H5) which are located inside the structured apolar regions of the proteins [28,29], are brought to the surface of the protein by a &turn structure and therefore are accessible to the protein kinase [ 131. The major sites of phosphorylation are placed outside the organised apolar regions of the proteins [29].…”
Section: Febs Lettersmentioning
confidence: 99%
“…The remaining 32P-label is found in the slightly basic N-terminal part of the molecule at the edge of the globular region of the protein (residues 23-99) [28].…”
mentioning
confidence: 99%
“…The specificity of these two enzymes contrasts sharply with that of cAMP-dependent protein kinase from pig brain which preferentially phosphorylates serine residues located in the globular domain (residues 22-100) of histone H5 [7,9]. Four of the 5 serine residues phosphorylated in vitro in H5 by the H1-specific cAMP-independent kinase are identical to those found phosphorylated in vivo [5].…”
Section: Resultsmentioning
confidence: 80%
“…Sites of phosphorylation of histone H5 have been investigated in vivo [4], and in vitro using the catalytic subunit of cyclic AMPdependent protein kinase from pig brain [7] and from rat pancreas [8]. Even if the specificity is different from one kinase to another, the sites of phosphorylation in histone H5 are distributed in vitro as in vivo in two distinct regions of the protein: the amino-terminal region (residues 1-21) and the carboxy-terminal region (residues 101-189); in all cases, no site has been detected in the globular part of the molecule (residues 22-100) [9]. This fact has been already mentioned for histone H 1 which, like histone H5, conrains 3 different domains: a short apolar amino-terrninal part in random coil (residues 1-34); a globular central part (residues 35-120); and a highly basic carboxy-terminal part in random coil (residues 121-213) [10].…”
Section: Introductionmentioning
confidence: 99%
“…The time-course of digestion was followed both by extraction with 5% perchloric acid (which extracts only histones Hl and H5 and their peptides) and by precipitation with trichloroacetic acid (which yields all chromosomal proteins). Fig.lB shows the rate of digestion of the lysine-rich histones set against a sample of pure histone H5 and a purified sample of the globular peptide of H5 obtained by a digestion in solution [9] and designated GHS: by 45 min the lysine-rich histones have been degraded to their limit peptides of which that from H5 presumably dominates. Detailed analysis of these limit products has shown that principally N-terminal residues are lost from core histones and that the resulting core particle is not dramatically changed in structure WI.…”
Section: Resultsmentioning
confidence: 99%